All You Need to Know About Climate Change - Yuri Di Liberto (Asimmetria, 2023)
What if I told you that they knew everything? And that they have known it for a very long time? On January 13 of this year, 2023, in the journal Science, perhaps the most important article to date on climate change was published. In political, social, and ethical terms, this article represents the equivalent of a nuclear bomb, despite the fact that (as is sadly obvious to expect) no one in mainstream news channels (and very few in academia) has mentioned it.
Keywords: P1; P18; Q4; Q5; Q54; 330; capital as power; climate; ExxonMobil; differential accumulation; sabotage